2020
DOI: 10.1136/ijgc-2019-000526
|View full text |Cite|
|
Sign up to set email alerts
|

Prognostic factors in patients with vulvar cancer: the VULCAN study

Abstract: ObjectiveThis study aimed to analyze the prognostic factors for overall and progression-free survival in patients with vulvar cancer.MethodsThis international, multicenter, retrospective study included 2453 patients diagnosed with vulvar cancer at 100 different institutions. Inclusion criteria were institutional review board approval from each collaborating center, pathologic diagnosis of invasive carcinoma of the vulva, and primary treatment performed at the participating center. Patients with intraepithelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…Vulvar carcinoma (VC) is a rare disease (5% of all gynecological neoplasms) with the highest incidence in the elderly, although, in recent years, the spread of human papilloma virus (HPV) infection in young women changed this trend [ 1 ]. Squamous cell carcinoma (SCC) is the most frequent histological type (90% of cases), although several rare entities such as melanoma, extra-mammary Paget’s disease, Bartholin’s gland adenocarcinoma, verrucous carcinoma, basal cell carcinoma (BCC), and sarcoma can occur [ 2 , 3 , 4 ]. Surgery is the standard treatment, frequently combined with neoadjuvant chemoradiation; alternatively, the treatment is based on exclusive chemoradiation, based on disease site and patient’s performance status [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vulvar carcinoma (VC) is a rare disease (5% of all gynecological neoplasms) with the highest incidence in the elderly, although, in recent years, the spread of human papilloma virus (HPV) infection in young women changed this trend [ 1 ]. Squamous cell carcinoma (SCC) is the most frequent histological type (90% of cases), although several rare entities such as melanoma, extra-mammary Paget’s disease, Bartholin’s gland adenocarcinoma, verrucous carcinoma, basal cell carcinoma (BCC), and sarcoma can occur [ 2 , 3 , 4 ]. Surgery is the standard treatment, frequently combined with neoadjuvant chemoradiation; alternatively, the treatment is based on exclusive chemoradiation, based on disease site and patient’s performance status [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the vulvar location is the most frequent site of female genital tract melanoma [ 2 ], representing approximately 1% of melanomas [ 6 ]. VMM has a poor prognosis and is the vulvar cancer type with the worst prognosis [ 3 ], especially in those with regional and distant metastatic disease [ 6 ]. Prognostic factors include disease stage, tumour size, patient age, comorbidities, and insurance status [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is attributable to patients delaying consultation [ 8 ]. Thus, late diagnosis considerably reduces the survival [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Surveillance, Epidemiology and End Results (SEER) study of 141 patients with FIGO stages I/II disease treated in 1999 reported that 47% of patients were treated with a radical vulvectomy [20]. More recently, a 2020 study, which included a cohort of 1535 patients treated for all stages of squamous vulvar cancer between 2001 and 2005 across 100 European centres reported radical vulvectomy in 76.5% and bilateral groin dissection in 45.2% of patients [21].…”
Section: Discussionmentioning
confidence: 99%